Designing and psychometric evaluation of Stretching Exercise Influencing Scale (SEIS). Issue 5 (22nd May 2019) - Delshad, Mohammad Hossien; Tavafian, Sedigheh Sadat; Kazemnejad, Anoshirvan
Abstract : Objective: The lack of reliable and valid tools for assessing the factors that influence stretching exercises (SEs) among Iranian office employees is obvious. This study aimed to design and evaluate psychometric properties of this instrument. Design: Cross-sectional study of psychometric properties. Setting: Data were gathered from May to September 2017. Participants: Participants were 420 office employees who were working in 10 health centres affiliated to the Shahid Beheshti University of Medical Sciences in Tehran, Iran. Primary outcome measures: The instrument was designed on the basis of the constructs of the health promotion model (HPM) and extant literature. Exploratory factor analysis (EFA), Cronbach's α and intraclass correlation coefficient (ICC) were employed to check the scale's psychometric properties. Results: In total, 420 questionnaires were completed. The mean age of the office employees was 37.1±8.03 years. Among the 86 items, 77 items had significant item-to-total correlations (p<0.05). The results showed good internal consistency and reliability for the whole questionnaire and each domain. EFA results confirmed 53.32% of the total variance of the items yielded in 11 subscales. The ICC was acceptable (0.78, 95% CI 0.70 to 0.88). Conclusions: The Stretching Exercise Influencing Scale (SEIS) can be a reliable and valid instrument for measuring the factors that influence SEs among office employees. Trial registration: IRCT20160824295512N1